GENDER RELATION IN MATRILINEAL KINSHIP PATTERNS IN THE OUTER ISLAND OF ENGGANO BENGKULU SUMATERA - Moch Iqbal (Indonesian Journal of Social Science Education (IJSSE), 2025)
The pattern of matrilineal kinship exists in several regions in Indonesia, the most well-known is in West Sumatra. However, in several other regions, there are also those who adhere to the matrilineal kinship pattern, namely several tribes in East Nusa Tenggara (NTT) and in the community of the outer island of Enggano Bengkulu. This paper wants to examine the kinship patterns on the remote and outermost islands of Enggano and the dynamics that exist in them. Using qualitative research methods with an ethnographic study approach; The results of this study are First, in general, the pattern of matrilineal kinship only exists in a few regions, although in general patrilineal kinship is still very dominant in Indonesian society. Second, the Enggano people are moving towards a more multicultural direction, along with the increasing number of immigrants from various ethnicities and religions.  Third, kinship in the Enggano community has been going on for a long time, and is still going on today, especially the local tribes. Fourth, there began to be a shift or relaxation in the application of matrilineal kinship in line with the arrival of immigrants and the penetration of technology in the Enggano community. Fifth, the role of women is still very significant in maintaining kinship patterns and household institutions.